PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SD NEGERI 147 PEKANBARU - Yunus, Muhammad; Noviana, Eddy; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low social science learning outcomes of students in class V B SD Negeri 147 Pekanbaru. Of the 35 students only 16 students reached the minimum completeness criteria (KKM), while the average score obtained by students was 69.86. Based on this emerging problem, the researchers conducted the study by applying a cooperative learning type pair check model. The purpose of this study is to improve social studies learning outcomes by applying a cooperative learning model type pair check. This research is a classroom action research (PTK) conducted in class V SD Negeri 147 Pekanbaru with 36 research subjects. The results showed that in the first cycle of meeting I the percentage of average teacher activity was 58%, the second meeting was 79%. While in the second cycle of meeting I the percentage of the average teacher activity was 83%, the second meeting the percentage was 87%. And in the first cycle of the first meeting the percentage of teacher activity was 54%, the second meeting was 70%. Whereas in the second cycle of the first meeting the average percentage was 83%, the second meeting of the student activities was 91. In addition to the basic score the average score of the students was 69.86 increasing to 73.57 in the first cycle, and increasing again to 78.14 in cycle II. Based on the results of the above research, it can be concluded that the application of the cooperative learning model type pair check can improve social studies learning outcomes of fifth grade students of SD Negeri 147 Pekanbaru.Key Words: Cooperative Learning Model Pair Check Type, Social Studies Learning Outcomes